PARENTAL AND SOCIAL FACTORS PREDICT THRIVING DURING THE TRANSITION TO UNIVERSITY - Gill, Harleen; Ritchie, Kerri; Gerhardt, Elizabeth; Wilson, Kaitlyn; Cameron, Catherine Ann (International Journal of Child, Youth and Family Studies, 2023)
This study investigated, through an attachment theoretical lens, the relationship between first-year university students’ personal and academic adjustment and 3 psychosocial resources: parental attachment, student resources (parental support, social support, ways of reducing loneliness, emotion regulation, coping strategies, locus of control), and gender. Participants answered questionnaires relating to their psychosocial resources and post-secondary adjustment in first and second term. These data were analysed using a planned regression analysis. In Term 1, paternal attachment predicted students’ emotional adjustment, with social and personal resources accounting for this relationship, and was related to academic adjustment via locus of control. Maternal attachment predicted academic adjustment. Gender and locus of control predicted academic performance (as measured by grade point average [GPA]). In Term 2, parental attachment predicted emotional adjustment, with social support accounting for this relationship, but academic adjustment was no longer related to paternal attachment. Overall, gender and locus of control predicted academic success. Suggestions are made for developing transitional theoretical models that address psychosocial processes that will help shape responsive institutional programming and planning in support of incoming college students. These recommendations include designing more personalized programs to match students and their family systems where possible and keeping parents/guardians informed of helpful supports for students’ experiences when needed.